2016
DOI: 10.3354/dao02945
|View full text |Cite
|
Sign up to set email alerts
|

Demodex castoris sp. nov. (Acari: Demodecidae) parasitizing Castor fiber (Rodentia), and other parasitic arthropods associated with Castor spp.

Abstract: A new species of demodecid mite, Demodex castoris sp. nov. (Acari: Prostigmata: Demodecidae), is described based on adult stages from the skin of the nasal region of the Eurasian beaver Castor fiber Linnaeus, 1758, collected in Poland. This is the first detection of a representative demodecid mite in rodents of the suborder Castorimorpha and also represents the first detection of a skin mite in Eurasian beavers. The new species is a small skin mite (average 173 µm in length) characterized by sexual dimorphism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…those whose evolution has been convergent with the evolution of the host species, the same species can be found in host species in different, sometimes distant, areas of its distribution. For instance, D. nanus Hirst, 1918 described from Europe was also found in the brown rat Rattus norvegicus (Berkenhout, 1769) in North America (Bukva 1987;1995;Desch 1987;Desch et al 2010;Izdebska et al 2013;Izdebska & Rolbiecki 2014b). In addition, in the case of the harbor seal, the same parasites were found in populations in very distant localities, e.g.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…those whose evolution has been convergent with the evolution of the host species, the same species can be found in host species in different, sometimes distant, areas of its distribution. For instance, D. nanus Hirst, 1918 described from Europe was also found in the brown rat Rattus norvegicus (Berkenhout, 1769) in North America (Bukva 1987;1995;Desch 1987;Desch et al 2010;Izdebska et al 2013;Izdebska & Rolbiecki 2014b). In addition, in the case of the harbor seal, the same parasites were found in populations in very distant localities, e.g.…”
Section: Discussionmentioning
confidence: 92%
“…Demodex lutrae Izdebska et Rolbiecki, 2014 in the Eurasian otter Lutra lutra (Linnaeus, 1758) and D. castoris Izdebska, Fryderyk et Rolbiecki, 2016 in the Eurasian beaver Castor fiber Linnaeus, 1758, described from Europe (Poland), and two species associated with marine mammals were found in Pinnipedia seals, i.e. D. phocidi Desch, Dailey et Tuomi, 2003 in the harbor seal Phoca vitulina Linnaeus, 1758 and D. zalophi Dailey et Nutting, 1979 in the California Sea lion Zalophus californianus (Lesson, 1828) in the United States of North America (Dailey & Nutting 1980;Desch et al 2003;Izdebska & Rolbiecki 2014a;Rolbiecki & Izdebska 2014;Izdebska et al 2016). However, D. phocidi was described on the basis of material collected from one seal originating from the USA (Alaska, Seward, Sea Life Center; Desch et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Among endoparasite helminth species, the flatworms Psilotrema castoris , Stichorchis subtriquetrus (Demiaszkiewicz et al 2014 ), Echinococcus multilocularis , Taenia martis (Campbell-Palmer et al 2015 ), Fasciola hepatica (Shimalov and Shimalov VT 2000); the nematode Travassosius rufus (Bystrianska et al 2021 ), Trichostrongylus capricola (Demiaszkiewicz et al 2014 ), Calodium hepaticum (Mészáros and Kemenes 1973 ; Fuehrer 2014 ), Trichinella spiralis (Różycki et al 2020 ) and Trichinella britovi (Seglina et al 2015 ) were found in C. fiber . Among ectoparasites, there are fur mites from the genus Schizocarpus , Demodex follicule mites (Izdebska et al 2016 ); two hard tick species Ixodes hexagonus (Haitlinger 1991 ) and Ixodes apronophorus (Kadulski 1998 ) and a unique epidermal tissue feeding beetle, Platypsyllus castoris (Åhlen et al 2021 ). Beavers can serve as a host for a wide range of rodent-related pathogens as well.…”
Section: Introductionmentioning
confidence: 99%
“…Demodex mites are ectoparasites residing on the mammalian skin. Two species of these mites only infect humans, namely Demodex folliculorum ( D. folliculorum ) and Demodex brevis ( D. brevis ) 1 …”
Section: Introductionmentioning
confidence: 99%